Rapid last-deglacial thinning and retreat of the marine-terminating southwestern Greenland ice sheet - Winsor,K; Carlson,AE; Caffee,MW; Rood,DH (EARTH AND PLANETARY SCIENCE LETTERS, 2015)
Marine-terminating outlet glaciers are a major source of modern ice loss from the Greenland Ice Sheet (GrIS), but their role in GrIS retreat during the last deglaciation is not well constrained. Here, we develop deglacial outlet glacier retreat chronologies for four regions in southwest and south Greenland to improve understanding of spatial variations in centennial- to millennial-scale ice loss under a warming climate. We calculate 10Be surface exposure ages of boulders located in fjords near the towns of Qaqortoq, Paamiut, Nuuk, and Sisimiut. Our northernmost study site, Sisimiut, deglaciated earliest at ∼18 ka to ∼15 ka with an average thinning rate of 0.1–0.3 m yr−1. Inland retreat from Sisimiut to the modern ice margin took ∼7 ka at an average retreat rate of 15–20 m yr−1. A 10Be-dated moraine ∼25 km from the modern GrIS margin deposited at ∼8 ka suggests a possible ice-margin still-stand, but this does not change overall retreat rates. After retreat from the small coastal Sisimiut fjords, the GrIS margin was mainly land-terminating in this region. In contrast, earliest exposure occurred at ∼12 ka near Qaqortoq, and 11–10 ka near Nuuk and Paamiut, with ice thinning at rates of 0.2–0.3 m yr−1 to instantaneous within measurement uncertainty. Ice retreat inland through the extensive Nuuk, Paamiut, and Qaqortoq fjord systems to near modern ice margins occurred in <1 ka, resulting in minimum retreat rates of 25–65 m yr−1 and maximum retreat rates of ∼95 m yr−1 to instantaneous within the uncertainty of our measurements. This rapid thinning and retreat of marine-terminating southwest GrIS margins is contemporaneous with an incursion of relatively warm ocean waters into the Labrador Sea and toward the southwest Greenland coast, suggesting that a warming ocean may have contributed to the more rapid retreat of marine GrIS termini in the Nuuk, Paa